An epidemiological study of overweight and obesity among women in an Urban area of North India - Sangeeta Girdhar; Sarit Sharma; Anurag Chaudhary; Priya Bansal; Mahesh Satija (Wolters Kluwer Medknow Publications, 2016)
Background: Obesity is a complex, multi-factorial chronic disease. Overweight and obesity are the fifth leading risk for global deaths. Objectives: To find the prevalence and risk factors for obesity in women aged 20-60 years in Ludhiana city. Methods: The present study is a community based cross sectional study carried out in an urban area of Ludhiana among women aged 20-60 years. Among the study population of 324 women, a pre-designed and pre-tested questionnaire was used to record the socio-demographic and anthropometric profile of women. Chi square test and logistic regression was used to find the association of obesity and hypertension with socio-demographic variables. Results: The prevalence of overweight and obesity was 12.7% and 29.6% respectively. Obesity was found to be more common among middle-aged Punjabi housewives belonging to upper socio-economic strata. There was strong association between overweight/obesity and hypertension.